Correlation of Pregnancy Associated Plasma Protein A and Zinc with Calculated Risk Ratio of Dual Test - Indranil Ghoshal; Bolar Suryakanth Varashree; Vijetha Shenoy Belle; Krishnananda Prabhu (Journal of Clinical and Diagnostic Research, 2017)
Introduction: First trimester screening by dual test is the most preferred method of antenatal screening. The detection rate of foetal aneuploidy using dual test is 95%. This test uses maternal serum free β human Chorionic Gonadotropin (free β hCG) and Pregnancy Associated Plasma Protein A (PAPP-A) along with maternal demographic and foetal sonographic indices to calculate risk for foetal aneuploidy. PAPP-A is a zinc binding metalloproteinase which is also responsible for placental development and foetal growth. So, zinc might also have some role in first trimester screening. No studies are available substantiating the role of zinc in first trimester screening. Aim: To measure and correlate maternal serum zinc with PAPP-A and calculated risk ratio of first trimester screening. Materials and Methods: PAPP-A and zinc were measured from the serum of 84 pregnant women aged 20-40 years in 11th-13th weeks+6 days of gestation who underwent dual test during their antenatal check-up. Risk calculation was done using Screening Software for Downs Windows Lab (SSDWL). Results: Maternal serum PAPP-A showed a significant positive correlation with maternal serum zinc (p-value <0.001). Maternal serum PAPP-A and zinc both showed a significant positive correlation with calculated risk ratio (p-value<0.01). Conclusion: As PAPP-A is a zinc binding metalloproteinase, zinc showed significant pattern of correlation with aneuploidy risk as shown by PAPP-A. So there could be a possible role for serum zinc in first trimester of screening.